(3JaSjQ (B( (3bd CYhP HQH GdfGS (B)s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bd GYhP HQH GdfGS bO PcQfG Gf GdQHhHjI YHGQI Yf GdJQHjI hGdJQHjI ETGQI Edi JbhjI GdeRGL aEf GdGfSGf dGjhLO YGdekG eSJYO GdHOf s
(3BNQgG (B:s
(3bhdg JYGdi (B: ( (3ef GdLfI hGdfGS (B) (3hGdGfS gh GdEjfGS hgeG ddMhGS GdXGgQI hGdHGWfI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B451s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs